Development of the Australian Dominant Drug Discourses Scale - Bright, Stephen; Kane, Robert; Bishop, Brian John; Marsh, Alison (Routledge, 2014)
There are a limited number of dominant discourses available to frame drug use within Australia. These dominant discourses play an important role in policy debate and development, and also drug use behaviour. We describe the development of a psychometric instrument that is hypothesised to measure the degree to which individuals internalise dominant drug discourses. Sixty items were developed to reflect six dominant discourses of drug use. A substantive validity analysis was conducted. The highest loading items were included in a 27-item measure that was administered to 370 people seeking substance use treatment in Perth, Western Australia. In addition, participants completed the Locus of Control of Behaviour Scale. Confirmatory Factor Analysis tested the fit of a predicted six factor model, in addition to three other plausible models. The best fitting model was the predicted model. Internal locus of control was correlated with medical and legal discourse. The Dominant Drug Discourses Scale appears to measure internalisation of six dominant discourses. The tool has utility in research examining policy development and drug use behaviours. To establish the construct validity of the tool and better understand the constructs being measured, further research is required.